2002
DOI: 10.1001/archotol.128.7.834
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the External Auditory Canal

Abstract: The outcome was related to the stage of disease, suggesting that the Pittsburgh staging system is useful also in patients with non-squamous cell carcinoma. Patients with early cancer benefited from a less aggressive surgical approach, while survival was poor in patients with advanced cancer with incompletely resected tumors despite adjuvant radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
93
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(103 citation statements)
references
References 10 publications
5
93
0
2
Order By: Relevance
“…Clearly, surgery combined with or without radiotherapy is widely accepted as the standard of treatment and previous reports found that radiotherapy alone or salvage surgery after radiotherapy had depressingly poor prognoses. [1,4,5] However, the results of these previous studies are limited by the small number of patients involved and too long periods of time required to collect these cases. Long periods of surveillance resulted in different qualities in imaging studies used for staging and different surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clearly, surgery combined with or without radiotherapy is widely accepted as the standard of treatment and previous reports found that radiotherapy alone or salvage surgery after radiotherapy had depressingly poor prognoses. [1,4,5] However, the results of these previous studies are limited by the small number of patients involved and too long periods of time required to collect these cases. Long periods of surveillance resulted in different qualities in imaging studies used for staging and different surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Many publications have tried to evaluate survival in this aggressive disease, but patient numbers are limited (ranging from 10 to 39 patients, with most <30 patients), and surveillance periods are too long (ranging from 10 to 37 years, with most >15 years), possibly due to the rarity of this disease. [1][2][3][4][5][6][7][8][9] The quality of imaging studies (Computed tomography (CT) and magnetic resonance imaging (MRI)) has improved dramatically over time, and the accuracy of diagnosis of this disease is influenced by the quality of imaging. Similar reports contain many patients, but they are multi-institutional retrospective studies, with the surgical procedure and the surgeon different at each institution and surveillance periods are too long (>20 years).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis for patients suffering from an auditory canal carcinoma is rather poor as described in the literature [14,15]. The total survival time (T1, T2 and T4) of our patients was 28.2 ± 6.4 (CI: 15.6-40.9) months.…”
Section: Discussionmentioning
confidence: 46%
“…All patients in the reconstruction of the EAC with STSG group showed preserved conformation of the new EAC for more than 12 months after surgery ( b ). apy alone or salvage surgery after radiotherapy [Kunst et al, 2008;Moody et al, 2000;Nyrop and Grøntved, 2002]. Sleeve resection, local canal resection (LCR) and LTBR are the most frequently applied surgical procedures in the management of patients with early-stage EAC carcinoma [Kunst et al, 2008;Yin et al, 2006;Zhang et al, 2013].…”
Section: Discussionmentioning
confidence: 99%